Assessment of contrast‐enhanced computed tomography for imaging of cartilage during fracture healing. Issue 4 (19th November 2012) - Hayward, Lauren N.M.; de Bakker, Chantal M.J.; Gerstenfeld, Louis C.; Grinstaff, Mark W.; Morgan, Elise F.
Abstract Assessment of the early stages of fracture healing via X‐rays and computed tomography is limited by the low radio‐opacity of cartilage. We validated a method of contrast‐enhanced computed tomography (CECT) for non‐destructive identification of cartilage within a healing fracture callus. Closed, stabilized fractures in femora of C57BL/6 mice were harvested on post‐operative day 9.5 and imaged ex vivo with micro‐computed tomography (µCT) before and after incubation in a cationic contrast agent that preferentially accumulates in cartilage due to the high concentration of sulfated glycosaminoglycans in the tissue. Co‐registration of the pre‐ and post‐incubation images, followed by image subtraction, enabled two‐ and three‐dimensional delineation of mineralized tissue, soft callus, and cartilage. The areas of cartilage and callus identified with CECT were compared to those identified with the gold‐standard method of histomorphometry. No difference was found between the areas of cartilage measured by the two methods (p = 0.999). Callus area measured by CECT was smaller than, but strongly predictive of (R2 = 0.80, p < 0.001), the corresponding histomorphometric measurements. CECT also enabled qualitative identification of mineralized cartilage. These findings indicate that the CECT method provides accurate, quantitative, and non‐destructive visualization of the shape and composition of the fracture callus, even during the early stages of repair when little mineralized tissue is present. The non‐destructive nature of this method would allow subsequent analyses, such as mechanical testing, to be performed on the callus, thus enabling higher‐throughput, comprehensive investigations of bone healing. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 567–573, 2013